Does herd behavior arise more easily under time pressure? Experimental approach - Lubomír Cingl (Charles University in Prague, Institute of Economic Studies (IES), 2012)
In this paper I explain individual's propensity to herd and infer its relationship to time-pressure by conducting a laboratory experiment. I let subjects perform a simple cognitive task under different treatment conditions and levels of time pressure with the possibility to herd. The order of decision-making sequence is endogenous and the nature of the task is not probabilistic; rather I impose the uncertainty of private signal by different levels of time pressure. This is expected to make participants prone to imitate the behavior of others. The main findings are that the propensity to herd was not significantly influenced by different levels of time pressure. Information cascades arose, but never in a perfect form. Personality traits contributed considerably to the explanation of the model, but their relationship is not straightforward and may need further research. Heart-rate significantly increased over the baseline during performance of a task, but was not correlated to the subjectively stated level of stress, which suggests that time pressure may not automatically induce stress but increase effort instead. Moreover, heart-rate is significantly associated with the propensity to herd, but unexpectedly with a negative sign.
Keywords: C25; C91; D03; D80; 330; information cascades; herding; experimental economics; heart rate measurement; personality traits